Relationship Between Directions Of Dysminora Pain To The Use Of Non-Steroid Anti-Inflammatory Medicines (Nsaids) On Adolescent Women In Environment Iii Of New Kelurahan Bamboo Field, Medan District Profit In 2019 - Sari Rahma Fitri; Dwi Ris Hasanah S S (Science Midwifery, 2022)
Menarche is the first menstruation experienced by women. Menarche is an early sign of the start of a new life as a teenager in puberty. Menstruation is a period of bleeding that occurs in women regularly every month during their fertile period unless pregnancy occurs. This study aims to determine the relationship between the degree of dysmenorrhea pain and the use of Non-Steroid Anti-Inflammatory Drugs (NSAIDs) in adolescent girls in Neighborhood III of Baru Ladang Bambu Village. The research method used is quantitative analytical approach. cross sectional, where the sample is 30 respondents through total sampling technique. The results of the bivariate analysis showed the degree of pain intensity, namely 8 respondents (26.6%) mild pain, 15 respondents (50.0) moderate pain, 7 respondents (23.4) severe pain. 19 respondents (63.3%) used NSAIDs. The results of the chi square statistical test obtained p = 0.027 this means that the p value is greater than the value and thus Ho is accepted and Ha is rejected. It is hoped that young women who are in Environment III of Ladang Bambu Village will further increase their knowledge about the use of NSAIDs to reduce pain during menstruation.